The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00253-010-2556-9
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and functional analysis of the second geranylgeranyl diphosphate synthase gene influencing helvolic acid biosynthesis in Metarhizium anisopliae

Abstract: A gene (ggs2) having high similarity to the geranylgeranyl diphosphate synthase (GGPP synthase) gene was cloned from Metarhizium anisopliae NAFF635007. The ggs2 gene (1,239-bp open reading frame with no intron) encoded a protein of 412 amino acids, and the transcription occurred only after late log-phase during the growth. Gene disruption of ggs2, performed to clarify the function in M. anisopliae, resulted in decreased GGPP synthase activity together with a slight delay of sporulation. An high performance liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…In contrast, mutants of B. bassiana with targeted disruptions of the peptide synthetase genes responsible for the biosynthesis of beauvericin and bassianolide were morphologically indistinguishable from WT, but the KO strains showed decreased virulence when tested against S. frugiperda, Helicoverpa zeae, and G. mellonella larvae (Xu et al 2008(Xu et al , 2009. Similarly, targeted gene knockout of a geranylgeranyl diphosphate synthase abolished the production of helvolic acid and reduced virulence of M. anisopliae NAFF635007 against two genera of insect larvae (Singkaravanit et al 2010).…”
Section: Discussionmentioning
confidence: 73%
“…In contrast, mutants of B. bassiana with targeted disruptions of the peptide synthetase genes responsible for the biosynthesis of beauvericin and bassianolide were morphologically indistinguishable from WT, but the KO strains showed decreased virulence when tested against S. frugiperda, Helicoverpa zeae, and G. mellonella larvae (Xu et al 2008(Xu et al , 2009. Similarly, targeted gene knockout of a geranylgeranyl diphosphate synthase abolished the production of helvolic acid and reduced virulence of M. anisopliae NAFF635007 against two genera of insect larvae (Singkaravanit et al 2010).…”
Section: Discussionmentioning
confidence: 73%
“…The biosynthetic mechanism of helvolic acid has not been fully understood. A loss-of-function study revealed that a geranylgeranyl diphosphate synthase (BAJ05823) is involved in the production of helvolic acid in M. anisopliae (Singkaravanit et al, 2010). Our genome survey indicated that the homolog of this protein is present not only in the non-specialists (e.g., MAA_03020 of M. robertsii , 82% identity) but also in M. acridum (MAC_02619, 80%) and M. album (MAM_05601, 75%).…”
Section: Discussionmentioning
confidence: 99%
“…Following on trypacidin, helvolic acid also exhibits antiprotozoal activity [67] and is produced by several fungal spp. in addition to A. fumigatus, including several plant and insect pathogens and many endophytes [28,68,69]. Along with gliotoxin and fumagillin, helvolic acid exhibits cilioinhibitory activity [70] and is a potent antimicrobial [71].…”
Section: Results and Discussion (A) Twenty-six Clustersmentioning
confidence: 99%